ショウワキチ デ カンソク シタ ビショウ ジシン - 神沼, 克伊; カミヌマ, カツタダ; KAMINUMA, Katsutada (国立極地研究所, 1971)
P(論文) Small shocks like micro-earthquakes are recorded frequently at Syowa Station. The small shocks are roughly classified into two types according to the initial motion. One has a sharp initial motion (type I) and the other has a weak one (type II). Some shocks of type I have a clear S phase and the rest have a small S phase. A swarm of type II shocks is recorded once or twice a year. The swarm occurs only in the summer season. With the data of February to December of 1969, ISHIMOTO-IIDA constant of the shocks of type II was calculated as m=1.99 using UTSU'S formula. It is established by MOGI that "m" increases with the degree of heterogeneity of the medium and also with the degree of spatial variation in the stress distribution of the field. The movement of the continental ice is active in the summer season and the structure may become heterogeneous. Thus, it is concluded that the shocks of type II are iceshocks (or icequakes). On the other hand, if a natural earthquake occurs around Syowa Station, its "m" is estimated at about 1.4, because the area belongs to the geological province of Pre-Cambrian gneiss, a part of the east Antarctic shield which is one of the non-seismic regions on the earth. departmental bulletin paper